MODEL PENINGKATAN DAYA TARIK WISATA MELALUI PENGEMBANGAN KUALITAS PELAYANAN PADA WANA - Salahuddin Salahuddin; Haifa Haifa; Hadi Jatmiko (STIE Mandala Jember, 2015)
Jemberhasseveral attractionsincludeCape Wana PapumaWatuUloBeach, Rembanganarea, beacharea ofNusaBarongandsomeagro-owned PT. Nusantaraplantationandsomehaveprivateestates. Management ofthese attractionsneed tobeoptimized. Tourism developmentis donetomakethemore interestingsightsandexcel. The purpose ofthe study: 1). FormulateStandard OperatingProcedure(SOP) travelservicesinCapePapumaWanaJember, 2). Testedagainststandard operatingprocedurespreparedand3). Analyzing thetraveler's satisfaction with the serviceatthe CapeecotourismPapumaJemberbeforeand after implementation ofthe SOP.Analysisandimprovement ofquality of careusing theprinciplesFocussGroup Discussions (FGD). To findthe differencebetweentouristsatisfactionbeforeand after implementation ofSOPdistributedquestionnairesto touristswhothenanalyzed byt-testanalysis showedno significant differencebetween thesatisfaction ofCapeecotourismtravelersPapumabeforeimplementationand after implementation ofStandard Operating Procedure(SOP). The analysis showedthatafterthe application ofSOP, ecotourismtourist satisfactionisthehighestPapumaCapeDimensionalTangible/Intangible(X1), thenthedimension ofEmpathy(X5), while thelowestsatisfactionratingisthedimensionRealibilty/Reliability(X2) andAssurance/warranty(X4). Thusthe managersWanaCapePapumais to maintainandenhance thetangibledimension/Tangible(X1) and theEmpathyDimension(X5) andincreaseDimensionsReliability(X2) andAssurance(X4), by regularlyconduct trainingtoimprove thequality of services tothe resourceshumansbothto employeesandpartners.MODEL PENINGKATAN DAYA TARIK WISATA MELALUI PENGEMBANGAN KUALITAS PELAYANAN PADA WANA